ANALYSIS OF ENGLISH TEACHERS’ ABILITY AND DIFFICULTY IN SPEAKING - Hendra Putra; Mustakim Sagita; Reski Hasan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2022)
This article analyzes about english teachers ability and difficulty in speaking. The purpose of this research to know ability and difficulty in speaking. This research uses qualitative approach with descriptive method. The total participants of this research is 22 participants and for the sample uses purpose sampling. In collecting data the authors use instruments. The instruments are speaking test and interview. Speaking test is used to know the ability english teachers and the interview is used to know the aspects of difficulty in speaking. The finding shows that english teachers ability in speaking is 63. It means that the ability english teacher is sufficient. From interviewing the aspect makes english teacher difficulties are communication strategy (not confidence when speaking). It can be concluded that english teachers ability need some strategies to improve ability in speaking.Keywords : english teachers ability, difficulty and speaking